EXPLORING OBESITY'S IMPACT ON QUALITY OF LIFE WITHIN SOUTH INDIAN SOCIETY (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
This research of quality of life of obesity patients in South Indian Communities was conducted to know the impact on their lifestyle and the etiology of the disease. This research is conducted to recognise the classification of overweight obesity as a major risk factor, to identify the epidemiology and reason for overweight and obesity increase. To understand the outlines for control and prevention of obesity. From this study we properly understand that the different complications related to obesity by case studies. The offline survey was conducted and data of 117 obesed patients were entered in electronic google form containing 21 questionnaires. A suitably designed data collection form was used to collect all the necessary information. The clinical outcome of the patient was measured at the end of the study. Individual patients’ signature was taken on consent form. The obtained data was subjected to suitable statistical analysis. The results were statistically analysed through pi-charts. Through which we recognised that obesed patients were mainly suffering from arthritis and high blood pressure. The main cause was due to genetics and hormonal imbalance where the patients undergo medication such as consumption of rosuvastatin or atorvastatin. Our research on South Indian communities revealed that over half of the population suffer from overweight or obesity, with body mass index being crucial. People engage in exercise and dietary changes for better health. We observed higher obesity rates in females, urban residents, and emphasized the need for public health strategies focusing on healthy eating, physical activity, and environmental interventions. Further research on motivations is key for behavioural changes against obesity.